Congenitally absent maxillary lateral incisors. A case report illustrating the use of a Mesialslider and a customised lingual appliance - Pies Stephan; Wilmes Benedict; Vasudavan Sivabalan (Sciendo, 2018)
A young adolescent female, aged 17 years and one month, presented seeking orthodontic treatment to address the congenital absence of her maxillary lateral incisors.